Regulation of Microbial Organisms in Australia – A Technical Overview - Barden, Graeme (Phytoprotection, 1998)
The National Registration Authority for Agricultural and Veterinary Chemicals (NRA) is the regulatory body responsible for the coordinated registration, regulation and review of agricultural and veterinary (agvet) chemicals up to and including the point of retail sale. This role is defined by the Agvet Code, 1994. Each of Australia's eight states and territories retains its own jurisdictional controls over the use of agricultural and veterinary products. The NRA may issue permits to exercise control over research agricultural and veterinary (agvet) chemicals. Under defined emergency conditions, the NRA can also issue "emergency use" permits, and can approve the use of agvet chemicals for minor uses that do not normally appear on product labels, and would otherwise be illegal. The Existing Chemicals Review Program of the NRA reviews registered agvet chemical products to ensure that they meet contemporary standards for efficacy, safety and health, and pose no undue risk to the environment or trade. Recently reviewed chemicals include atrazine, metham sodium, endosulfan and ethylene dibromide, and certain changes to their registration and labelling are being implemented. Several other chemicals are currently under review. The Special Review Program allows the NRA to review registered agvet products if there are any special issues arising that may alter the terms of their original registration. Current challenges to the NRA include the management of insecticide and weed resistance, particularly in relation to the regulation of genes expressing insecticides and herbicide tolerance. Specific guidelines for the registration of microbiological products are currently being reviewed. Issues relating to the release of microbial organisms into existing agricultural Systems and environments require considered risk assessment prior to any approval. Macrobiological control agents are specifically excluded from regulation by the NRA. They may, however, be regulated under other pieces of legislation.